Developing Post-operative Assessment Skills in Japanese Undergraduate Nursing Students Using High-fidelity Simulator (Sim Man) - A Pilot Study - Yukiko Orii (Halla Newcastle Education and Research Center, 2014)
In this study we attempted to analyse whether or not high-fidelity simulated training was useful for improving the students' abilities of clinical judgment and/or decision-making. Curriculum implementation can be enhanced by offering nursing students an opportunity to perform suites of nursing skills in a simulated environment. It is true that simulation training should not be a substitute for actual practices in the clinical settings, but it can at least give students a chance to convert "knowledge" into "skills" by the use of experiences in the settings that mirror actual practice. The provision of repeated training helped study participants' confidence and improved their clinical judgment.